Implementation of a Medication Adherence Program (MAP) in the Primary Care Setting for Adults Diagnosed with Hypertension - Harrell, Regina (My University, 2017)
Medication adherence is a significant problem in primary care. The primary care site chosen for this project reported poor patient medication adherence was related to age, health literacy, socioeconomic status, and/or polypharmacy. The purpose of this project was to develop and implement a medication adherence program (MAP) for adults diagnosed with hypertension in the primary care setting. This performance improvement project involved provider education and training on all components of the MAP program and implementation of the MAP protocol with medication adherence screening and education sessions provided for eligible clinic patients. Pender’s Health Promotion Model was used to guide this project. The Plan-Do-Study-Act (PDSA) rapid cycle of improvement was used weekly to evaluate the 90-day implementation process. Seventy-eight percent of MAP patients indicated that they sometimes forget to take their antihypertensive medications. Behavioral risk was the most commonly identified medication adherence risk factor. After initiation of the MAP, 56% of patients showed improved medication adherence. Project findings indicate that MAPs can improve medication adherence for patients in the primary care setting diagnosed with hypertension. Utilizing a person-centered approach, medication adherence programs can improve individual medication adherence that consequently improves overall health outcomes for the community.